Ethiopian University Students', Lecturers' and Administrators' Perceptions of Interculturally Competent Persons - Ayana, Desta; Sercu, Lies (African Journal of Education and Practice, 2023)
Purpose: This study's aim was to investigate Ethiopian university students', lecturers', and administrators' perceptions of the dispositions (savoir-être) of interculturally competent persons. Methodology: Building on seminal models of intercultural competence, a survey instrument was created to inquire into the three stakeholder groups' perceptions. The survey was completed by 638 participants. Findings: The paper highlights similarities and differences between students, lecturers, and administrators. The findings also show that African and western characteristics associated with interculturally competent persons reflect the respondents' personal and professional roles. Unique Contribution to Theory, Practice and Policy: This study is the first to study Ethiopian students', lecturers' and administrators' perceptions of interculturally competent persons. The study's findings provide a baseline on which curricula and policies can build in order to promote intercultural competence in Ethiopian universities.